October 1917: A Changing Landscape for Peasant Literature. The Role of the Journal Na postu (ENTHYMEMA, 2022)
The article analyzes the role of the journal Na Postu in the complicated and in many ways conflictual transition from a peasant literature, in the 1930s declared as kulak literature, to the literature of kolchoz. The journal Na postu provided a forum for discussion and debate, at time heated, developing along lines which, in light of current knowledge and the concept of governmentality elaborated by M. Foucault, allow us to rework certain viewpoints that have proven inadequate to interpreting Soviet literature from the 1920s.
Keywords: Soviet Literature; Peasant Literature; Soviet Literary Criticism; Foucault; Govern-mentality